2018
DOI: 10.4049/immunohorizons.1800018
|View full text |Cite
|
Sign up to set email alerts
|

Basophils Are Dispensable for the Control of a Filarial Infection

Abstract: Basophils are innate effector cells that contribute to allergic reactions and provide protection against parasites. Using basophil-deficient Mcpt8-cre mice, we have previously shown that these granulocytes contributed to the immune mediated early control of the gastrointestinal helminth Strongyloides ratti in mice. In this study, we analyze the impact of basophils on the immune response and defense against the tissue-dwelling filarial helminth parasite Litomosoides sigmodontis. Although basophils and IgE incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Basophils were also not required for the initiation of a Th2 response to Schistosoma mansoni in constitutive basophil-deficient Basoph8 x Rosa-DTa mice [27] or Mcpt8-Cre mice [28]. Moreover, Litomosoides sigmodontis infection, a model for human filarial infections [29] elicited comparable cellular and humoral immune responses and was cleared with similar kinetics in basophil-deficient Mcpt8-Cre mice and Mcpt8-WT mice [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basophils were also not required for the initiation of a Th2 response to Schistosoma mansoni in constitutive basophil-deficient Basoph8 x Rosa-DTa mice [27] or Mcpt8-Cre mice [28]. Moreover, Litomosoides sigmodontis infection, a model for human filarial infections [29] elicited comparable cellular and humoral immune responses and was cleared with similar kinetics in basophil-deficient Mcpt8-Cre mice and Mcpt8-WT mice [11].…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that, although clearly contributing to the early expulsion of Strongyloides adults from the intestine, basophils play only a minor role in the final control and termination of infection [4, 7]. Also intestinal parasite burden during a primary infection with Nippostrongylus brasiliensis , Heligmosomoides polygyrus , Trichinella spiralis and Litomosoides sigmodontis were not affected by basophil deficiency or depletion [811]. However, several lines of evidence suggest a contribution of basophils in the generation and execution of the protective immune response during a secondary infection with N .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that IgE, that is known to activate mast cells by crosslinking of the high-affinity IgE receptor, is increased during L . sigmodontis infection as well [ 16 ]. Nevertheless, the absence of mast cells in Cpa3 cre mice did neither change the vascular permeability induced by blood-sucking mites nor the number of L4 or adult parasites in the thoracic cavity at any time point during L .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have previously shown an increase of polyclonal IgE in the serum and an increase of L . sigmodontis -specific IgE locally in the thoracic cavity [ 16 ] until day 90 p.i. Thus, a repeated activation of mast cells during chronic L .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation